THE DYNAMICS OF PRODUCTION COSTS AND VARIANCE PERFORMANCE IN THE OIL PALM INDUSTRY IMPLICATIONS FOR OPERATIONAL SUSTAINABILITY - Hamzah Manurung; Hafizhah Risnafitri; Erinka Ayu Pratiwi; Syifa Az Zahra Manurung (CV. Radja Publika, 2025)
This research aims to calculate the Cost of Goods Manufactured (COGM) for Fresh Fruit Bunches (FFB) and analyze the components influencing cost variations at the Adolina Plantation, PT. Perkebunan Nusantara IV Regional II. The study specifically evaluates the gap between actual production costs and planned budgets to determine operational efficiency. A quantitative comparative method was employed, utilizing variance analysis to compare actual work realization against the Work Plan and Budget (RKAP) for the period 2022–2024. Production costs were categorized into direct costs (harvesting, maintenance, and fertilization) and indirect costs (salaries, administration, and depreciation). The results reveal that the average COGM at Adolina Afdeling IV was IDR 1,586 per kilogram. While total nominal production costs decreased following a reduction in operational area, the unit cost showed a constant upward trend—rising from IDR 1,489 in 2022 to IDR 1,648 in 2024. This increase was primarily driven by a sharper decline in production volume relative to cost reductions. Variance analysis identified favorable conditions in 2022 (5.14%) and 2023 (0.39%), whereas 2024 exhibited an unfavorable variance of -0.001% due to increased labor costs and delayed fertilization schedules caused by extreme weather. Despite fluctuations in production volume and climate-related challenges, the plantation maintained a healthy average profit margin of IDR 1,107 per kilogram. The study concludes that controlled cost management is essential to ensuring operational sustainability and economic value in the face of volatile agricultural productivity.